Quality of life for cancer chemotherapy patients at PZAGA Mahajanga hospital - Refeno, Valéry; Randrianarisoa, Rova M. F.; Bakohariliva, Hasina Andrianarivony; Rakotondranaivo, Harimanana F. F.; Rasamimanana, Naharisoa G.; Rafaramino, Florine (International Journal of Research in Medical Sciences, 2025)
Background: Cancer chemotherapy is often associated with adverse effects that may be responsible for impaired quality of life. Our aim was to describe the quality of life of patients undergoing cancer chemotherapy at PZAGA Hospital in Mahajanga. Methods: This was a prospective descriptive study conducted between November 1, 2019 and October 31, 2020, including patients who had received chemotherapy. The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C30 (EORTC QLQ-C30) was used. Results: Forty-six patients agreed to participate in the study. The mean age of the patients was 48.02±14.16 years, with a sex ratio of 0.24. The mean global health status score was 70.83±22.69. For the functional scales, mean scores were 82.90±21.35 (physical functioning), 76.45±33.62 (role functioning), 78.08±19.27 (emotional functioning), 84.06±16.08 (cognitive functioning), and 95.29±10.34 (social functioning). For the symptom scales, mean scores were 21.15±22.15 (fatigue), 11.23±23.32 (nausea and vomiting), 20.29±26.27 (pain), 4.35±13.35 (dyspnea), 19.57±31.09 (insomnia), 15.22±26.95 (appetite loss), 13.04±27.65 (constipation), and 2.17±10.89 (diarrhea). For financial difficulties, the mean score was 42.03±32.53. Conclusions: The overall quality of life of the patients was good. The disparity in the scores obtained calls for a search for the most vulnerable groups in order to adapt the management.